Faktor Faktor Determinan Yang Berpengaruh Terhadap Kecurangan Laporan Keuangan - Jordan Tirta Jaya; Murtanto Murtanto; Hermi Hermi (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine whether financial target, financial stability, nature of industry, ineffective monitoring, change in auditor, change in director, frequent number of CEO's picture and state-owned enterprises influence the practice of financial statement fraud in healthcare sector companies registered on the IDX in 2019-2022. The sample used in this research consisted of 16 healthcare sector companies with 64 annual reports and 64 financial reports. The samples selected used purposive sampling technique. The data analysis method used in this research is multiple linear regression analysis. The research results show that financial targets, ineffective monitoring and state-owned enterprises have a positive effect on financial statement fraud, while the nature of industry has a negative effect on financial statement fraud, for financial stability, change in auditor and change in director do not have a positive effect on financial statement fraud and frequent number of CEO's pictures do not have a negative effect on financial statement fraud.